Legal-historical view of the protection of mere possession in Serbian law - Gavrilović, Biljana (Glasnik Advokatske komore Vojvodine, 2020)
Subject of this analysis is a legal – historical view of the protection of mere possession in Serbian law, from the enactment of the Serbian Civil Code (1844) to 1941. The protection of mere possession was primarily criminal during the second half of the 19th and early 20th centuries. There were just a few paragraphs about protection of mere possession in the Serbian Civil Code (1844), and they all were indistinct. Moreover, there were no special paragraphs about protection of mere possesion in the Code of Civil Procedure (1865). But, since the entry into force of the Yugoslav Code of Civil Procedure, the mere possession had enjoyed adequate, civil protection.